2016
DOI: 10.1039/c6ce01464j
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective amplification on circularly polarized laser-induced chiral nucleation from a NaClO3solution containing Ag nanoparticles

Abstract: We demonstrate that a statistically-significant chiral bias in NaClO 3 chiral crystallization can be provoked by inducing nucleation via the optical trapping of Ag nano-aggregates using a continuous wave visible circularly polarized laser (λ = 532 nm). The laser was focused at the interface between air and an unsaturated NaClO 3 aqueous solution containing Ag nanoparticles. The "dominant" enantiomorph was switchable by changing the handedness of the incident circularly polarized laser, indicating that the chir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 60 publications
1
42
0
Order By: Relevance
“…When one-handed circularly polarized light, which has been emitted from various sources (Bonner 1991;Bailey et al 1998), was used to irradiate ice grains with nanoparticles during α-CO formation, the resulting crystal enantiomeric excess might be several tens of per cent. This suggestion could be supported by laboratory experiments on NaClO 3 chiral crystallization (Niinomi et al 2016;Cheng et al 2020) and theoretical studies (Tang & Cohen 2010;Liu et al 2015;Ho et al 2016). The peak attributed to circular dichroism of the chiral molecule, which generally lies in UV region, could be transferred to the visible wavelength region in these cases (Zhang & Govorov 2013;Wang et al 2014;Vestler, Ben-Moshe & Markovich 2019).…”
Section: O U T L O O Kmentioning
confidence: 75%
“…When one-handed circularly polarized light, which has been emitted from various sources (Bonner 1991;Bailey et al 1998), was used to irradiate ice grains with nanoparticles during α-CO formation, the resulting crystal enantiomeric excess might be several tens of per cent. This suggestion could be supported by laboratory experiments on NaClO 3 chiral crystallization (Niinomi et al 2016;Cheng et al 2020) and theoretical studies (Tang & Cohen 2010;Liu et al 2015;Ho et al 2016). The peak attributed to circular dichroism of the chiral molecule, which generally lies in UV region, could be transferred to the visible wavelength region in these cases (Zhang & Govorov 2013;Wang et al 2014;Vestler, Ben-Moshe & Markovich 2019).…”
Section: O U T L O O Kmentioning
confidence: 75%
“…Thus, LIPS is likely to be related to a string of recent laserinduced nucleation experiments claiming to use optical trapping of clusters, 15,17,19,61,62,[70][71][72][73][74] although these experiments could only be carried out at air-solution interfaces, implying that evaporation, Marangoni effects, and thermophoresis may play important roles as well. A repeat of these experiments in the bulk would be worthwhile, bearing in mind the possibility of a hidden liquidliquid critical point enhancing concentration fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially demonstrated that circularly polarized light could induce a bias during the chiral crystallization of NaClO 3 . 269 A few years later, Chen et al used non-chiral gold triangle trimers in a saturated solution of sodium chlorate illuminated with RCP or LCP light to obtain a crystalline enantiomeric excess of more than 50%. 270 In a follow-up paper, the same group explained this result by modeling the plasmonic near-field during illumination and showing that the large enantiomeric excess previously observed arose from a difference in the frequency of attachment of chiral crystalline clusters to crystal nuclei, or in the local concentration of NaClO 3 due to chirally biased diffusion, rather than from enantioselective optical trapping.…”
Section: Chiral Catalysismentioning
confidence: 99%